2008
DOI: 10.3892/ijmm.21.6.785
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen on bone resorption and inflammation in the temporomandibular joint cellular elements

Abstract: Abstract. Several epidemiological studies have reported that temporomandibular disorder is more prevalent in women, which suggests the involvement of sex hormones, such as estrogen, in the pathogenesis of this disease. PCR amplification and Western blotting were employed to target the expression of estrogen receptors (ERs) in human fibroblast-like synovial and ATDC5 cells. The effect of estrogen was investigated through the expression of RANKL, osteoprotegerin (OPG), M-CSF/CSF-1 and c-fms. We showed expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…The study used mouse chondrogenic ATDC5 cells, which are an excellent in vitro model for studying the regulation of endochondral bone growth as they undergo similar differentiation processes with chondroprogenitor cells in the growth plates fully differentiating into hypertrophic chondrocytes in the presence of insulin (Snelling et al 2010). The findings that both ERs and OBRs are expressed in ATDC5 cells (Kishida et al 2005, Galal et al 2008) also suggest that ATDC5 cells are an appropriate model for studying the cross talk between leptin and estrogen. In our previous study (Wang et al 2011), we found that both ERa and ERb were dynamically expressed during the ATDC5 cell differentiation from 4 to 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…The study used mouse chondrogenic ATDC5 cells, which are an excellent in vitro model for studying the regulation of endochondral bone growth as they undergo similar differentiation processes with chondroprogenitor cells in the growth plates fully differentiating into hypertrophic chondrocytes in the presence of insulin (Snelling et al 2010). The findings that both ERs and OBRs are expressed in ATDC5 cells (Kishida et al 2005, Galal et al 2008) also suggest that ATDC5 cells are an appropriate model for studying the cross talk between leptin and estrogen. In our previous study (Wang et al 2011), we found that both ERa and ERb were dynamically expressed during the ATDC5 cell differentiation from 4 to 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…87 It has been shown that 17␤-estradiol has a positive effect on OPG transcription and an inhibitory effect on TNF-␣ liberation. 88,89 We have previously reported on the presence of estrogen imbalance in a group of female patients with severe condylar resorption. 13 Evidence also suggests that nutritional status may be an important determinant of an individual's susceptibility to degenerative TMJ disease.…”
Section: Susceptibility To Condylar Resorptionmentioning
confidence: 98%
“…Diagnosis and the cure of TMJOA is complex and mixed because the disease is accompanied with synovitis, apticular capsulitis, anterior disc displacement and perforation of articular disc 5,6) . Wikes stages are determined by the placement and morphology of the articular disc and the bone destruction of hip process shown in TMJ MRI 7) .…”
Section: Discussionmentioning
confidence: 99%